EXPLORING THE ROLE OF SHARIA-BASED SOCIAL MEDIA REPUTATION IN SHAPING BANK ALADIN SYARIAH'S CUSTOMER TRUST - Supriadi; Nur Isra' Ahmad; Ismawati; Asyraf Mustamin (Academic Bright Collaboration, 2026)
The main purpose of this study is to explore the role of social media reputation in shaping customer trust in Bank Aladin Syariah. The research method used in this study is qualitative and exploratory. The data in this study was collected through in-depth interviews with customers who actively follow Bank Aladin Syariah's Instagram account, as well as observations of content uploaded by banks. The analysis is carried out in several stages, namely determining the topic, coding the data, grouping data by category and finally formulating conclusions. The three main findings that emerged from this exploration are: first, the credibility of the content is the foundation of trust. Second, visual branding that carries a modern and Islamic image. Third, the interactivity and responsiveness of the Bank Aladin Syariah Instagram account. The findings highlight that social media plays a strategic role in building value-based trust rather than mere promotion. Bank Aladin Syariah should manage its digital reputation through credible content, appealing visuals, and interactive communication. The study’s limitation lies in its focus on Instagram and predominantly young informants, suggesting future research across platforms with more diverse participants. This study has originality because it examines in depth the role of Sharia-based social media reputation in shaping customer trust in Bank Aladin Syariah. The focus on the Instagram platform provides a unique contribution, considering that this visual-interactive social media is rarely studied specifically in the context of digital Islamic banking.